Sulfation of opioid drugs by human cytosolic sulfotransferases: Metabolic labeling study and enzymatic analysis - Kurogi, Katsuhisa (Eur J Pharm Sci, 2014)
The current study was designed to examine the sulfation of eight opioid drugs, morphine, hydromorphone, oxymorphone, butorphanol, nalbuphine, levorphanol, nalorphine, and naltrexone, in HepG2 human hepatoma cells and human organ samples (lung, liver, kidney, and small intestine) and to identify the human SULT(s) responsible for their sulfation. Analysis of the spent media of HepG2 cells, metabolically labeled with [(35)S]sulfate in the presence of each of the eight opioid drugs, showed the generation and release of corresponding [(35)S]sulfated derivatives. Five of the eight opioid drugs, hydromorphone, oxymorphone, butorphanol, nalorphine, and naltrexone, appeared to be more strongly sulfated in HepG2 cells than were the other three, morphine, nalbuphine, and levorphanol. Differential sulfating activities toward the opioid drugs were detected in cytosol or S9 fractions of human lung, liver, small intestine, and kidney, with the highest activities being found for the liver sample. A systematic analysis using eleven known human SULTs and kinetic experiment revealed SULT1A1 as the major responsible SULTs for the sulfation of oxymorphone, nalbuphine, nalorphine, and naltrexone, SULT1A3 for the sulfation of morphine and hydromorphone, and SULT2A1 for the sulfation of butorphanol and levorphanol. Collectively, the results obtained imply that sulfation may play a significant role in the metabolism of the tested opioid drugs in vivo.